Pharmacological management of IPF. Issue 4 (12th April 2016) - Borie, Raphael; Justet, Aurelien; Beltramo, Guillaume; Manali, Effrosyni D.; Pradère, Pauline; Spagnolo, Paolo; Crestani, Bruno
Abstract: Idiopathic pulmonary fibrosis (IPF) is a deadly disease with a median survival of approximately three years in historical cohorts. Despite increased knowledge of disease pathophysiology and selection of more targeted therapy, main clinical trials yielded negative results. However, two agents, pirfenidone and nintedanib, were recently shown to be effective in IPF and received marketing authorization worldwide. Both drugs significantly reduce functional decline and disease progression with an acceptable safety profile. Yet, none of these drugs actually improves or even stabilizes the disease or the symptoms perceived by the patient. Several other treatments and combinations are currently tested, and many more are ready for clinical trials. Their completion is critical for achieving the ultimate goal of curing patients with IPF.